Solve for p (p-6)/3=-15

Math
p-63=-15
Multiply both sides of the equation by 3.
3⋅p-63=3⋅-15
Simplify both sides of the equation.
Tap for more steps…
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3⋅p-63=3⋅-15
Rewrite the expression.
p-6=3⋅-15
p-6=3⋅-15
Multiply 3 by -15.
p-6=-45
p-6=-45
Move all terms not containing p to the right side of the equation.
Tap for more steps…
Add 6 to both sides of the equation.
p=-45+6
Add -45 and 6.
p=-39
p=-39
Solve for p (p-6)/3=-15

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top